[Afisz. Incipit] Rolniku! Cały nasz kraj tętni ... (Gdańsk : [wydawca nieznany], 1953)
Afisz propgandowy kierowany do chłopów.
Keywords: Propaganda -- Polska -- 1945-1970 -- druki ulotne; Gdańsk (Polska ; region) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.